Laparoscopic extraction of a urethral self-inflicted needle from pelvis in a boy: a case report - Wang, Xiaoqing; Wu, Xiangyu; Liu, Wei; Du, Guoqiang; Wang, Yanze; Wu, Rongde; Guo, Feng (Frontiers in Pediatrics, 2023)
Introduction Self-insertion of foreign bodies in the urethra is an infrequent occurrence in children, and their management aims to minimize urethral morbidity. Endoscopic removal presents a significant challenge, particularly in boys. Currently, there are few reports on laparoscopic management of urethral foreign bodies that have migrated to the pelvic cavity. Case Description An 11-year-old boy presented to the emergency department with complaints of increased frequency of micturition and dysuria. A sharp sewing needle was discovered lodged in the posterior urethra mucosa during cystoscopy. Attempts to remove the needle using an endoscopic grasping forceps were unsuccessful due to the forceps' weak biting power. During a digital rectal examination, the needle migrated into the pelvic region, wedged between the prostatic urethra and the rectal ampulla. After careful inspection of the peritoneal reflection over the fundus of the bladder, the needle was identified and successfully removed through laparoscopy without any complications. Psychiatric counseling was advised for this patient, who was in good condition during an 8-week follow-up. Conclusions Our case demonstrates the first recorded use of laparoscopy to remove a self-inserted urethral needle that had migrated into the pelvic region, after failed attempts at endoscopic extraction. Future cases may benefit from considering laparoscopic interventions for similar circumstances.